The CD48 receptor mediates Staphylococcus aureus human and murine eosinophil activation. Issue 11 (November 2014) - Minai‐Fleminger, Y.; Gangwar, R. S.; Migalovich‐Sheikhet, H.; Seaf, M.; Leibovici, V.; Hollander, N.; Feld, M.; Moses, A. E.; Homey, B.; Levi‐Schaffer, F.
Summary Background Allergy is characterized by eosinophilia and an increased susceptibility to microbial infection. Atopic dermatitis (AD) is typically associated with Staphylococcus aureus (SA) colonization. Some of the mechanisms by which SA and its exotoxins interact with eosinophils remain elusive. CD48, a glycosylphosphatidylinositol‐anchored receptor belonging to the CD2 family, participates in mast cells–SA stimulating cross‐talk, facilitates the formation of the mast cell/eosinophils effector unit and as expressed by eosinophils, mediates experimental asthma. Objective To investigate the role of CD48 expressed on human peripheral blood and mouse bone marrow‐derived eosinophils (BMEos) in their interaction with heat‐killed SA and its three exotoxins, Staphylococcal enterotoxin B (SEB), protein A (PtA) and peptidoglycan (PGN). Methods Eosinophils were obtained from human peripheral blood and BM of WT and CD48−/− mice. SA was heat killed and eosinophils–SA/exotoxins interactions were analyzed by confocal microscopy, adhesion and degranulation, cell viability, cytokine release and cell signalling. In addition, peritonitis was induced by SEB injection into CD48−/− and WT mice. CD48 expression was studied in AD patients' skin and as expressed on their leucocytes in the peripheral blood. Results We provide evidence for the recognition and direct physical interaction between eosinophils and SA/exotoxins. Skin of AD patients showed a striking increase of eosinophil‐associated CD48 expression while on peripheral blood leucocytes it was down‐regulated. SA/exotoxins enhanced CD48 eosinophil expression, bound to CD48 and caused eosinophil activation and signal transduction. These effects were significantly decreased by blocking CD48 on human eosinophils or in BMEos from CD48−/− mice. We have also explored the role of CD48 in a SEB‐induced peritonitis model in CD48−/− mice by evaluating inflammatory peritoneal cells, eosinophil numbers and activation. Conclusions These data demonstrate the important role of CD48 in SA/exotoxins–eosinophil activating interactions that can take place during allergic responses and indicate CD48 as a novel therapeutic target for allergy and especially of AD.